Dichtungs-, Kunst- und Künstlertheorie in Ferdinand von Saars lyrischem und erzählerischem Werk: [The Theory of Poetry, Art, and the Artist in Ferdinand von Saar’s Lyrical and Narrative Work] (Studia theodisca, 2017)
This essay deals with the implicit poetical annotations and thoughts in some lyrical and narrative works of Ferdinand von Saar. His theoretical statements about art, literature or the position of artists and writers in modern society are few in number. So it is important to search in his literary works for some indication of his attitude towards poetical theory. This paper includes poems and so-called artist novels, like Für den Leiermann, Tambi and Sühnefall. These texts demonstrate the liminal position of Ferdinand von Saar between tradition and modernity and his own theoretical reflections about it.